2010
DOI: 10.1002/dta.112
|View full text |Cite
|
Sign up to set email alerts
|

An improved validated ultra high pressure liquid chromatography method for separation of tacrolimus impurities and its tautomers

Abstract: A selective, specific and sensitive ultra high pressure liquid chromatography (UHPLC) method was developed for determination of tacrolimus degradation products and tautomers in the preparation of pharmaceuticals. The chromatographic separation was performed on Waters ACQUITY UPLC system and BEH C₈ column using gradient elution of mobile phase A (90:10 v/v of 0.1% v/v triflouroacetic acid solution and Acetonitrile) and mobile phase B (90:10 v/v acetonitrile and water) at a flow rate of 0.6 mL min⁻¹. Ultraviolet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…Although there is extensive literature on the determination and characterization of tacrolimus process related compounds and some potential degradation products [17,18,[23][24][25][26][27][28][29], practically no attention has been paid to the impurities that originate from drug-excipient interactions. The main purpose of this work was to investigate influence of commonly used excipients on degradation of TAC.…”
Section: Introductionmentioning
confidence: 99%
“…Although there is extensive literature on the determination and characterization of tacrolimus process related compounds and some potential degradation products [17,18,[23][24][25][26][27][28][29], practically no attention has been paid to the impurities that originate from drug-excipient interactions. The main purpose of this work was to investigate influence of commonly used excipients on degradation of TAC.…”
Section: Introductionmentioning
confidence: 99%
“…Several methods have been reported for the analysis of TAC-related substances and degradation products (14,15,19,20). In the United States Pharmacopeia (USP) official monograph of TAC and TAC-capsules, two high performance liquid chromatography (HPLC) methods are described for the analysis of TAC organic impurities, since not all potential impurities could be measured by one method alone (14).…”
mentioning
confidence: 99%
“…In the European Pharmacopoeia (EP) monograph, a gradient method with a run time of 53 min is described and is applied for the TAC drug substance only (15). The most promising pre-existing method applied for pharmaceutical formulations seemed to be a UHPLC method with a total run time of 25 min developed by Subasranjan et al (20), where efficient separation of four known impurities from TAC and its equilibrium compounds was demonstrated. In our previous work, we used a fast UHPLC method for evaluation of TAC incompatibility with excipients (13).…”
mentioning
confidence: 99%
“…Ascomycin has immunosuppressant properties similar to tacrolimus, which fundaments its determination. In addition, it has been reported that the drug tautomerizes, yielding related rearrangement products [238,239], and the analysis can be further complicated by the presence of mixtures of interconverting rotamers [240].…”
Section: Impurities Resulting From Degradation Of Natural Product Apismentioning
confidence: 99%